POTENTIALLY INAPPROPRIATE MEDICATION IN ELDERLY OUTPATIENT OF TERTIARY HOSPITAL IN INDONESIA - Yosi Febrianti; Eko Budi Setiawan; Ninisita Srihadi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Increased percentage of geriatric population has an impact on more health issues. The older the geriatrics, the more susceptible they are to various physical complaints due to either natural factors or diseases. To described the prevalence of potentially inappropriate prescriptions in geriatric outpatients A retrospective, cross-sectional study was done for three months in the Medical Record Department, in one of tertiary hospitals in Indonesia. The data was analyzed using Beers Criteria 2012 and described as descriptive statistics. A total 400 prescriptions were collected in the study during the period of 3 months. The estimated prevalence of potentially inappropriate prescription use in tertiary hospitals in Indonesia reached 24.5%. The most common potentially inappropriate prescription were nonsteroidal anti-inflammatory drugs (NSAID) (17 %) and benzodiazepine (12%). NSAID was the most prescribed potentially inappropriate agents of 66 events.